2013
DOI: 10.1177/2167702612463566
|View full text |Cite
|
Sign up to set email alerts
|

Novel Models for Delivering Mental Health Services and Reducing the Burdens of Mental Illness

Abstract: Most individuals in both developing and developed countries who experience mental illness do not receive psychological services. The dominant model of delivering services used in developed countries (individual therapy by a highly trained mental health professional) can provide effective (i.e., evidence-based) treatments but is greatly limited as a means of reaching the large swath of individuals in need. We highlight several models outside the mental health professions (e.g., public health, medicine, business… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
290
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(298 citation statements)
references
References 119 publications
1
290
0
7
Order By: Relevance
“…This approach meets urgent calls to improve global mental health by training nonspecialists to address unmet mental health needs. 46,47 These same calls also highlight needs to integrate mental health screening or services into primary health care settings. Although pediatricians are uniquely well positioned to screen mothers of patients with disabilities, multiple challenges remain in doing so.…”
Section: Discussionmentioning
confidence: 99%
“…This approach meets urgent calls to improve global mental health by training nonspecialists to address unmet mental health needs. 46,47 These same calls also highlight needs to integrate mental health screening or services into primary health care settings. Although pediatricians are uniquely well positioned to screen mothers of patients with disabilities, multiple challenges remain in doing so.…”
Section: Discussionmentioning
confidence: 99%
“…Parte de este esfuerzo debe provenir de usar m茅to-dos de intervenci贸n a trav茅s de Internet, smartphones, etc. (Kazdin y Rabbitt, 2013), junto con la necesaria mejora de los tratamientos ya existentes. Los procedimientos de MSC pueden integrarse bien en esta direcci贸n.…”
Section: Discussionunclassified
“…Kazdin and colleagues (Kazdin, 2016;Kazdin & Blase, 2011;Kazdin & Rabbitt, 2013) have also observed that we collectively need to address another critical gap. They note that our field's emphasis on treatment, particularly one-on-one psychotherapy delivered by expert (i.e., master's or doctoral) providers, creates a treatment-gap-or a discrepancy between those who could benefit from services and those who receive them.…”
Section: The Mission Of the Association For Behavioral Andmentioning
confidence: 99%
“…But, as noted by Patel (2014), we already know enough to make a meaningful global difference if we expend more resources in other directions. Sample recommendations proposed to increase our impact include an increased focus on prevention and public health approaches, the use of strategic research to change public policy, and utilization of scalable strategies to increase the reach of what we currently have (Brownell & Roberto, 2015;Fairburn & Patel, 2014;Fairburn & Wilson, 2013;Kazdin & Blase, 2011;Kazdin & Rabbitt, 2013;Lyon & Koerner, 2016;Patel, 2014;Patel, Chowdhary, Rahman, & Verdeli, 2011;Zandberg & Wilson, 2013). Scalability refers to the degree to which interventions can be scaled-up to reach large populations without significant loss of effectiveness.…”
Section: The Mission Of the Association For Behavioral Andmentioning
confidence: 99%